Presenting an Extended Model of Money Laundering Control According to Factors Related to Transparency in the Banking System of Islamic Republic of Iran (Case study of Melli Bank of Iran) - Torabian, Abdolmehdi (2021)
The aim of this study is to present an extended model of money laundering control according to the factors related to transparency in the banking system of Melli Bank of Iran. Accordingly, in this study, the factors affecting money laundering control were first identified through exploratory studies and survey of experts familiar with the subject using Delphi technique, and then, these factors were tested in the form of a model designed in the statistical population. The statistical population of the study to test the model included all 321 senior managers of Melli Bank branches in Kerman province, 200 of whom were selected as the sample through a convenience random sampling method. The present study is a descriptive-survey study conducted using field method. Also, this research is applied-developmental in terms of objective. The method of data collection in this study was a combination of library and field studies and data were collected through reviewing of documents, interviews and questionnaires (2 questionnaires) that their validity and reliability of were confirmed with a high percentage. The research data were analyzed using SPSS and AMOS 22 software. The research results confirmed the research model and showed that controlling and supervising foreign currencies, creating a powerful organization, providing statistical reports, the role of supervisors and transparency in financial and administrative systems are effective in controlling money laundering.